39. NON-SMALL CELL LUNG CANCER WITH SIMULTANEOUS EGFR AND PIK3CA GENE MUTATIONS: PRELIMINARY TREATMENT RESULTS AT NATIONAL LUNG HOSPITAL FROM 2022 TO 2024 (Vietnam Journal of Community Medicine, 2024)
Introduction: Targeted therapy treatment in non-small cell lung cancer patients significantly improves survival and quality of life for patients with EGFR mutations The coexistence of EGFR/PIK3CA mutations is considered a factor affecting the efficacy of EGFR-TKIs treatment in patients with non-small cell lung cancer (NCSLS).Methods: The cross-sectional descriptive study was conducted on 6 patients with concurrent EGFR and PIK3CA mutations at the National Lung Hospital.Results: 6/8 patients (75%) had EGFR Del19 mutations, 2/8 patients had L858R mutation. The mean age of the study group was 63.4 years, with 3 male patients (37.5%) and 5 female patients (62.5%). 4/8 patients (50%) had PIK3CA exon 9 mutations, 2/8 patients (25%) had PIK3CA exon 4 mutation. The remaining 2 patients respectively carried PIK3CA exon 2 and exon 20 mutations. The median progression-free survival (PFS) was 10.2 months and overall response rate (ORR) was 62,5%, with 2/8 patients (25%) becoming resistant and treated with second-line chemotherapy and palliative care. There were no serious adverse effects in these patients.Conclusion: The use of EGFR-TKIs as first-line treatment was effective in this group of EGFR/ PIK3CA co-mutated patients.
Keywords: Non-small cell lung cancer (NCSLS), co-mutation, EGFR, PIK3CA, EGFR TKI, initial treatment.